ENHANCING URBAN MICRO-MOBILITY: ENVIRONMENTAL IMPACT OF INTEGRATED BIKE SHARING AT COMMUTER RAIL STATIONS IN YOGYAKARTA URBANIZED AREA - Damar Pratita Dewayanto; Derin Marshall (Jurnal Pengembangan Kota, 2024)
Climate change, particularly CO2 emissions from the transportation sector, poses a significant global challenge. Promoting micro-mobility services, especially bike sharing programs, is crucial in addressing this issue. This study examines the environmental benefits of integrating bike sharing programs with public transportation by estimating the potential CO2 emission reductions through the avoided motorized trips approach. Data were collected via a commuter line passenger survey in the Yogyakarta Urbanized Area, resulting in 157 valid responses. The estimation considered specific data inputs: trip distance, emission factor, energy factor of transportation mode, and the number of people traveling by mode. Two scenarios related to bike sharing demand and commuter line ridership were employed. The findings reveal that bike sharing demand ranges from 16.03% to 48.08%. In terms of CO2 emissions reduction, the study indicates that avoided motorized trips through bike sharing as an egress mode can potentially reduce cumulative CO2 emissions by up to 567,158.35 tons CO2e by 2030. This reduction corresponds to 0.487% and 160.113% of the national and provincial reduction targets, respectively. These findings provide insightful information to promote sustainable transportation provision.